Green packaging and green advertising as precursors of competitive advantage and business performance among manufacturing small and medium enterprises in South Africa - Eugine Tafadzwa Maziriri (Cogent Business & Management, 2020)
This research aimed to assess the impact of green packaging and green advertising on competitive advantage and business performance of manufacturing Small and Medium-sized Enterprises (SMEs). A research conceptual model was produced to determine the relationships from that model. A quantitative research approach was utilised for this investigation and a simple random sampling procedure was embraced. The target population for this examination was confined to heads of marketing departments within manufacturing SMEs in the Gauteng province of South Africa. The data analysis was done in Statistical Package for Social Sciences (SPSS) 25 for demographic data analysis and AMOS 25 was utilised for the structural equation modelling. The tested relationships produced satisfactory results consistent with how they were hypothesised. Unequivocally, it was discovered that green packaging and green advertising had a positive influence on competitive advantage and business performance. This investigation expands the knowledge base that presently exists in the field of green marketing, competitive advantage, as well as SMEs business performance. Likewise, this examination is important to manufacturing SME proprietors and supervisors since most them endeavour to have a competitive advantage and additionally, to boost profitability, as well as the business' interest.
Keywords: M3; M31; M37; 650; green packaging; green advertising; competitive advantage; business performance